2006
DOI: 10.1529/biophysj.105.079640
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Ca2+-ATPase and the Pentameric Form of Phospholamban in Two-Dimensional Co-Crystals

Abstract: Phospholamban (PLB) physically interacts with Ca(2+)-ATPase and regulates contractility of the heart. We have studied this interaction using electron microscopy of large two-dimensional co-crystals of Ca(2+)-ATPase and the I40A mutant of PLB. Crystallization conditions were derived from those previously used for thin, helical crystals, but the addition of a 10-fold higher concentration of magnesium had a dramatic effect on the crystal morphology and packing. Two types of crystals were observed, and were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
75
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 48 publications
16
75
1
Order By: Relevance
“…7D). Although several studies show that phospholamban asserts its inhibitory function by binding to SERCA in its monomeric form (2,24,25) there is some evidence that the pentameric form of phospholamban may directly interact with SERCA2a, causing a decrease in the affinity of the pump for Ca 2ϩ (45,52). However, the mechanism of this interaction is not fully understood.…”
Section: Vlcad Deficiency In Mice Leads To Polymorphic and Bidirectiomentioning
confidence: 99%
“…7D). Although several studies show that phospholamban asserts its inhibitory function by binding to SERCA in its monomeric form (2,24,25) there is some evidence that the pentameric form of phospholamban may directly interact with SERCA2a, causing a decrease in the affinity of the pump for Ca 2ϩ (45,52). However, the mechanism of this interaction is not fully understood.…”
Section: Vlcad Deficiency In Mice Leads To Polymorphic and Bidirectiomentioning
confidence: 99%
“…Our studies had focused on the monomeric mutant to study the complex with SERCA, given that the monomer is believed to be responsible for inhibition, as well as to eliminate potential complex equilibria between various oligomers of wt-PLN. However, recent studies suggested that the pentameric form of PLN could play a larger role in SERCA regulation than previously was thought (5). Therefore, we embarked in the elucidation of the structure and topology of the pentamer in lipid bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the mixture of R14del and wild-type PLN was similar to SERCA in the presence of only R14del (Table 1). For comparison, we evaluated a loss-of-function mutant in the transmembrane domain of PLN, Arg 34 3 Ala (N34A) (46). The persistent effect on SERCA seen for the R9C and R14del mutants was not observed with N34A (supplemental Fig.…”
Section: Table 1 Kinetic Parameters From Hill Plotsmentioning
confidence: 99%